Computational intelligence and bioengineering : essays in memory of Antonina Starita - Masulli, Francesco; Micheli, Alessio; Sperduti, A. (Allesandro); Starita, A. (Antonina) (Amsterdam ; Washington, DC : IOS Press)
Includes bibliographical references and indexes.